2019
DOI: 10.1177/0193945918824070
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing How Intensive Care Unit Nurses Allocate Their Time

Abstract: Spending time with the patient is essential for intensive care unit (ICU) nurses to detect clinical change. This article reports on an examination of factors influencing nurses’ activity time allocation. Data were analyzed from a prospective time and motion study of medical ICU nurses. Nurse demographic data and observation, electronic locator technology, and electronic medical record log data were collected over 12 days from 11 registered nurses. Charlson Co-Morbidity Index and Sequential Organ Failure Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 62 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…The SOFA score has good predictive validity for inpatient mortality with higher scores associated with higher mortality (Ferreira et al, 2001). According to the previous research done by Despins, Kim, Deroche, and Song (2019), nurses spent more time in patients' rooms with higher SOFA scores. This result is similar to another study done by (Altafin et al, 2014), who found that as SOFA scores increased, the time consumed by nursing activities increased.…”
Section: Prior Literaturementioning
confidence: 89%
See 3 more Smart Citations
“…The SOFA score has good predictive validity for inpatient mortality with higher scores associated with higher mortality (Ferreira et al, 2001). According to the previous research done by Despins, Kim, Deroche, and Song (2019), nurses spent more time in patients' rooms with higher SOFA scores. This result is similar to another study done by (Altafin et al, 2014), who found that as SOFA scores increased, the time consumed by nursing activities increased.…”
Section: Prior Literaturementioning
confidence: 89%
“…This outcome might be explained by frequent interruptions during the out-of-room activities. ICU nurses with low experience could be interrupted more often outside the patient room compared to highly experienced nurses (Farquharson et al, 2013;Hall et al, 2010). It is also possible that ICU nurses with low experience may have less time management skills than highly experienced nurses (Pellico, Brewer, & Kovner, 2009).…”
Section: The Impact Of Nementioning
confidence: 99%
See 2 more Smart Citations
“…Working in an intensive care unit is a considerable source of pressure and psycho‐social stress because of the lack of natural lighting, excessive noise, the large number of professionals and clinical equipment, high patient mortality, the lack of tangible results of the care provided by nurses and the constant need for adequate decision‐making (Bahadori et al, 2014). These factors, associated with the characteristics of patients in critical condition and the workload, can negatively impact nurses (Despins et al, 2019; Myny et al, 2011; Towell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%